Penerapan SAK EMKM Dalam Penyusunan Laporan Keuangan UD Tirta Surya - Chyntia Dewi Nur Oktavia; Rr. Adiati Trihastuti (Akuntansi, 2024)
UD Tirta Surya is an individually owned trading business engaged in refill water. SAK EMKM is one of the financial accounting standards that has been issued by the Financial Accounting Standards Board of the Indonesian Institute of Accountants with the aim of making it easier for business actors, especially MSMEs, to record financial statements. This research was conducted using a qualitative method with a descriptive approach and the data used were primary data and secondary data. The purpose of this research was conducted to determine the recording of financial statements carried out by UD Tirta surya and to determine the application of SAK EMKM in recording UD TIRTA SURYA's financial statements. The results obtained in this study are that UD Tirta Surya still uses simple recording so that the preparation of financial reports made is still not in accordance with SAK EMKM.